Arthroscopic Saucerization of Discoid Lateral Meniscus, With Meniscus Repair as Indicated, Results in Excellent Outcomes in Pediatric Patients Younger Than 12 Years of Age - George A. Rublev, M.D.; Levan Natchkebia, M.D.; Vazha Gaprindashvili, M.D.; Mohamed Ahmed Mohamed, M.D.; Tamaz Tamazishvili, M.D.; Irakli Kartozia, M.D.; Mikheil Zimlitski, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: To evaluate the experiences and outcomes of arthroscopic partial meniscectomy in symptomatic non-Wrisberg discoid lateral meniscus in children younger than 12 years old at a single center. Methods: We retrospectively reviewed the medical records of all pediatric patients who were treated for non-Wrisberg discoid meniscus at our institute between 2013 and 2021. Patients were separated into 2 groups: Patients who underwent partial resection with saucerization (group A) or patients who underwent saucerization, tear repair, and fixation (group B). Clinical outcomes were compared between the 2 groups. Results: A total of 20 patients (22 knees) were treated for non-Wrisberg discoid meniscus and included in this study. Nine patients underwent partial resection with saucerization (group A) whereas 11 patients underwent saucerization, tear repair, and fixation (group B). The average follow-up was 3 years (range 2-10 years). The results showed that 17 of the 20 patients had excellent outcomes whereas the other 3 had good outcomes after a minimum follow-up of 2 years. The average Knee Injury and Osteoarthritis Outcome Score for Children score was 93. Conclusions: Arthroscopic saucerization of symptomatic non-Wrisberg discoid lateral meniscus, with additional repair as indicated results in excellent or good outcomes in children younger than 12 years of age. Level of Evidence: Level III, case–control study.